1998
DOI: 10.1038/32911
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the human leptin receptor gene causes obesity and pituitary dysfunction

Abstract: The adipocyte-specific hormone leptin, the product of the obese (ob) gene, regulates adipose-tissue mass through hypothalamic effects on satiety and energy expenditure. Leptin acts through the leptin receptor, a single-transmembrane-domain receptor of the cytokine-receptor family. In rodents, homozygous mutations in genes encoding leptin or the leptin receptor cause early-onset morbid obesity, hyperphagia and reduced energy expenditure. These rodents also show hypercortisolaemia, alterations in glucose homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
1,095
5
116

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,107 publications
(1,239 citation statements)
references
References 33 publications
23
1,095
5
116
Order By: Relevance
“…Acute dietary fasting also profoundly suppresses serum leptin levels and attenuates the leptin pulse area and incremental pulse amplitude (Bergendahl et al, 2000). In humans, as in mice, congenital absence of leptin or functional leptin receptor causes severe obesity accompanied by neuroendocrine abnormalities (Montague et al, 1997;Strobel et al, 1998;Ozata et al, 1999;Clement et al, 1998). Interestingly, the neuroendocrine defects that are present in leptin-deficient rodents and in leptin-resistant humans differ from each other, which indicates that the role of leptin in mediating the neuroendocrine response to starvation may be different in humans versus rodents (Montague et al, 1997;Strobel et al, 1998;Ozata et al, 1999;Clement et al, 1998).…”
Section: Leptinmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute dietary fasting also profoundly suppresses serum leptin levels and attenuates the leptin pulse area and incremental pulse amplitude (Bergendahl et al, 2000). In humans, as in mice, congenital absence of leptin or functional leptin receptor causes severe obesity accompanied by neuroendocrine abnormalities (Montague et al, 1997;Strobel et al, 1998;Ozata et al, 1999;Clement et al, 1998). Interestingly, the neuroendocrine defects that are present in leptin-deficient rodents and in leptin-resistant humans differ from each other, which indicates that the role of leptin in mediating the neuroendocrine response to starvation may be different in humans versus rodents (Montague et al, 1997;Strobel et al, 1998;Ozata et al, 1999;Clement et al, 1998).…”
Section: Leptinmentioning
confidence: 99%
“…In humans, as in mice, congenital absence of leptin or functional leptin receptor causes severe obesity accompanied by neuroendocrine abnormalities (Montague et al, 1997;Strobel et al, 1998;Ozata et al, 1999;Clement et al, 1998). Interestingly, the neuroendocrine defects that are present in leptin-deficient rodents and in leptin-resistant humans differ from each other, which indicates that the role of leptin in mediating the neuroendocrine response to starvation may be different in humans versus rodents (Montague et al, 1997;Strobel et al, 1998;Ozata et al, 1999;Clement et al, 1998). Data from Chan et al (2003) has suggested that a reduction of circulating leptin levels in lean men regulates the acute fasting-induced changes that occur in the HPG axis and, in part, the changes that occur in the hypothalamic-pituitarythyroid (HPT) axis and in IGF-1-binding capacity, but it is not responsible for changes in the HPA, rennin-aldosterone, and GH-IGF-1 axes associated with acute fasting (Chan et al, 2003).…”
Section: Leptinmentioning
confidence: 99%
“…14 Hypothalamic hypothyroidism is seen at a young age with a subsequent failure to undergo pubertal development due to hypogonadotropic hypogonadism. Mutations in the leptin receptor result in a comparable phenotype, 15 although are not necessarily associated with elevated serum leptin concentrations (personal communication). Although leptin deficiency appears to be rare, it is entirely treatable with daily subcutaneous injections of recombinant human leptin with beneficial effects on appetite, fat mass and hyperinsulinaemia, reversal of the immune defects and infection risk and allowing the appropriate development of puberty 14 (Figure 1).…”
Section: Congenital Leptin and Leptin Receptor Deficiencymentioning
confidence: 99%
“…[53][54][55] Mutations in the human Ob-Rb also produce morbid obesity. 56 Importantly, the gene expression of the Ob-Rb is evident in the mediobasal hypothalamic sites including the arcuate nucleus. [57][58][59][60] The leptin receptor has also been identified in the human brain.…”
mentioning
confidence: 99%